Narrative Policy Framework: Indonesia’s Capital City Relocation Policy - Inrinofita Sari; Suswanta Suswanta (Magister Ilmu Administrasi Publik, 2023)
The issue of the relocation of Indonesia's capital city has garnered increasing coverage by the Indonesian news media. The media has a crucial position in shaping public narratives concerning policymaking. Furthermore, it is well known that news media has an influential role in shaping public narratives especially in public policy process. This study uses Narrative Policy Framework (NPF) to examine the general public and policymaking actors narrative in news media related to the issue of Indonesia’s capital city relocation. This study uses qualitative research methods with the QDAS (Qualitative Data Analysis Software) approach. The data sources used for this study is collected from five widely-known online news media in Indonesia. The findings of this study indicate that the pro-side who support the decision to relocate the capital city is more influential. Through actors who are pro towards the policy, the most significant pro narrative is found in the indicators of Equitable Development and Economy. Relocating the capital city to Kalimantan is claimed to be one of the solutions implemented by the Jokowi government to balance the development on the island of Java and outside Java. Meanwhile, the main narrative in the opposing side (cons) is that relocating the capital city is not urgent because it cannot be implemented in time and that the economic downturn due to the COVID-19 pandemic still overshadows Indonesia's economic conditions.